Herpes Simplex Virus Type 1 ICP27 Induces p38 Mitogen-Activated Protein Kinase Signaling and Apoptosis in HeLa Cells - Gillis, Peter A. (American Society for Microbiology (ASM), 2009)
The herpes simplex virus type 1 (HSV-1) protein ICP27 has been implicated in a variety of functions important for viral replication including host shutoff, viral gene expression, activation of mitogen-activated protein kinases p38 and Jun N-terminal protein kinase (JNK), and apoptosis inhibition. In the present study we sought to examine the functions of ICP27 in the absence of viral infection by creating stable HeLa cell lines that inducibly express ICP27. Here, we characterize two such cell lines and show that ICP27 expression is associated with a cellular growth defect. The observed defect is caused at least in part by the induction of apoptosis as indicated by caspase-3 activation, annexin V staining, and characteristic changes in cellular morphology. In an effort to identify the function of ICP27 responsible for inducing apoptosis, we show that ICP27 expression is sufficient to activate p38 signaling to a level that is similar to that observed during wild-type HSV-1 infection. However, ICP27 expression alone is unable to lead to a strong activation of JNK signaling. Using chemical inhibitors, we show that the ICP27-mediated activation of p38 signaling is responsible for the observed induction of apoptosis in the induced cell lines. Our findings suggest that during viral infection, ICP27 activates p38 and JNK signaling pathways via two distinct mechanisms. ICP27 directly activates p38 signaling, leading to stimulation of the host cell apoptotic pathways. In contrast, robust activation of JNK signaling by ICP27 requires one or more delayed early or late viral gene products and may be associated with the inhibition of apoptosis.